Analisis Karakter Siswa Pembelajaran Matematika di Kelas 2 SD Negeri 2 Batur - Ni Nyoman Pitayani; I Nyoman Sudirman; I Nyoman Artadana; Ni Luh Made Dwi Prayanti (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to analyze the Analysis of Student Character in Mathematics Learning in Grade 2 of Elementary School 2 Batur in 2024. This research method is a qualitative descriptive research method. The data of this study were collected using interview, observation and documentation techniques. The subjects in this study were grade 2 students of Elementary School 2 Batur. The results of this study indicate that the character of curiosity and perseverance is a disciplined character in students. In addition, there is a significant positive relationship between the character of curiosity and perseverance and mathematics learning achievement. Factors that influence the formation of student character include teacher teaching style, family environment, and peers. This study provides important implications for teachers in designing learning that can develop student character and improve mathematics learning achievement. Mathematics learning in grade 2 in general in Learning has been going well, Character is needed so that students are able to become intelligent and good people. In addition, character is also needed as capital in facing the digital era with fierce competition. Mathematics learning can be a means of getting used to character education, namely through learning in which problem solving questions are given. Giving this character is expected to become a habit in students so that students have good character.